Enabling and improving trans-nerolidol production by Corynebacterium glutamicum: combining metabolic engineering and trace elements medium refinement - Seeger, Jan; Lohoff, Stella; Schmitfranz, Fabian; Henke, Nadja A.; Wendisch, Volker F. (Frontiers in Bioengineering and Biotechnology, 2025)
Terpenes are biomolecules of significant industrial relevance, with applications in pharmaceuticals, cosmetics, and the food industry. Their biotechnological production is emerging, with Corynebacterium glutamicum, a Gram-positive bacterium traditionally employed for large-scale amino acid production, serving as a promising host. While metabolic engineering strategies have been extensively applied to enhance terpene titers in C. glutamicum, the role of medium composition, particularly trace elements, remains underexplored. In this study, the impact of trace element composition on trans-nerolidol production by engineered C. glutamicum was investigated. A Design of Experiments (DoE) approach identified MgSO4 as a critical factor, and the refined trace element composition led to a 34% increase in trans-nerolidol production. Further metabolic engineering efforts resulted in a final titer of 28.1 mg L-1. Subsequent fed-batch fermentation achieved a trans-nerolidol titer of 0.41 g L-1, representing the highest reported sesquiterpene titer being produced by C. glutamicum to date. Additionally, the refined trace element composition was successfully applied to patchoulol- and (+)-valencene-producing strains, leading to production increases of 15% and 72%, respectively. These findings demonstrate that trace element refinement and metabolic engineering act as complementary strategies for enhancing terpene production in a microbial production host.